A recent epidemiological cluster of acute hepatitis B genotype F1b infection in a restricted geographical area of Italy. (December 2015) - Pollicita, M.; Alteri, C.; Bellocchi, M.C.; Armenia, D.; Carioti, L.; Salpini, R.; Colagrossi, L.; Battisti, A.; Aragri, M.; Fabeni, L.; Mariani, R.; Dalessandro, M.; et al.
Abstract: In this study, by phylogenetic analysis, we identified an epidemiological cluster involving eight individuals diagnosed with acute hepatitis B virus (HBV) infection related to unprotected sexual intercourse in a restricted area of central Italy (time period: 2011–2014). Notably, these patients (six of eight Italians) were infected by subgenotype F1b, which is not commonly found in western countries. Ultra-deep pyrosequencing confirmed a superimposable composition of HBV quasi-species in these patients. Despite the availability of effective vaccination, this study highlights the importance of not underestimating the risk of HBV infection, of continuing to set up surveillance programmes for HBV infection, and of investigating the pathogenetic potential of these atypical genotypes.